Роль та функції стратегічного управлінського обліку в системі стратегічного управління підприємством - Рубан, Ліна Олегівна; Чуприна, Людмила Вікторівна (НТУ "ХПІ", 2016)
У статті досліджено економічну сутність і призначення стратегічного управлінського обліку на підприємстві. Узагальнено існуючі концепції щодо місця і ролі стратегічного управлінського обліку в інформаційному забезпеченні управління суб'єктів господарювання. Визначено роль стратегічного управлінського обліку та стратегічного аналізу в процесі прийняття стратегічних управлінських рішень. Визначено функції та задачі стратегічного управлінського обліку на підприємстві. Доведено, що саме стратегічний управлінський облік, використовуючи інструменти стратегічного аналізу, задовольняє потреби менеджменту в інформаційному забезпеченні розробки бізнес-стратегій.

The management accounting in ХХ century was directed on the internal management. The strategic management accounting provides not only with necessary information for the production, the marketing, the research and the development but also offers the analyses of activity considering strategic goals, uses methods of obtaining the information about critical success factors: the quality, the innovation, the time est. for the enterprise development’s strategy optimization. In the article economic essence and purpose of strategic management accounting at the enterprise were investigated. Concepts of the role of strategic management accounting in information support management of business entities were gene ralized. The role of strategic management accounting and strategic analysis in making strategic management decisions has been defined. Functions and tasks of strategic management accounting at the enterprise were identified. Proved that strategic management accounting, using the tools of strategic analysis, meets the needs of information support management in developing business strategies.
The role and functions of management accounting in system of strategic management
Keywords: облік управлінський; аналіз стратегічний; планування стратегічне; контроль стратегічний; забезпечення обліково-аналітичне; рішення стратегічне; рішення управлінське; управління стратегічне; management accounting; strategic analysis; strategic planning; accounting-analytical support; strategic management